Expression and Immunogenicity of the Mycobacterial Ag85B/ESAT-6 Antigens Produced in Transgenic Plants by Elastin-Like Peptide Fusion Strategy. (13th April 2010) - Floss, Doreen Manuela; Mockey, Michael; Zanello, Galliano; Brosson, Damien; Diogon, Marie; Frutos, Roger; Bruel, Timothée; Rodrigues, Valérie; Garzon, Edwin; Chevaleyre, Claire; Berri, Mustapha; Salmon, Henri; et al.
Abstract : This study explored a novel system combining plant-based production and the elastin-like peptide (ELP) fusion strategy to produce vaccinal antigens against tuberculosis. Transgenic tobacco plants expressing the mycobacterial antigens Ag85B and ESAT-6 fused to ELP (TBAg-ELP) were generated. Purified TBAg-ELP was obtained by the highly efficient, cost-effective, inverse transition cycling (ICT) method and tested in mice. Furthermore, safety and immunogenicity of the crude tobacco leaf extracts were assessed in piglets. Antibodies recognizing mycobacterial antigens were produced in mice and piglets. A T-cell immune response able to recognize the native mycobacterial antigens was detected in mice. These findings showed that the native Ag85B and ESAT-6 mycobacterial B- and T-cell epitopes were conserved in the plant-expressed TBAg-ELP. This study presents the first results of an efficient plant-expression system, relying on the elastin-like peptide fusion strategy, to produce a safe and immunogenic mycobacterial Ag85B-ESAT-6 fusion protein as a potential vaccine candidate against tuberculosis.